Diagnosis of Horn Cancer through Thermography and It’s Surgical Management in Cattle - A Dave, Harshad; V Vadalia, Jignesh; T Fefar, Dhaval; H Bhatt, Raghuvir; R Padaliya, Nilesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Horn cancer is one of the most prevalent cancers among all neoplastic conditions impacting the bovine population and productivity.  A reduction in draught performance, milk production and general well-being leads to considerable economic loss to the farmers. The  present study was aimed to diagnose horn cancer early through thermography and its timely surgical management in cattle. The present  study involved 34 cases of first-degree horn cancer in bullocks (31/34) and cows (3/34) presented at the Veterinary College Clinic in  Junagadh (Gujarat, India) and the area around Junagadh during the year 2024. The study revealed the highest incidence of horn cancer  in Gir and Kankrej cattle (47.06% each) predominantly affecting castrated male animals (91.18%). In cases with first-degree horn cancer,  shaking of the head, rubbing of the horn on hard objects, nasal discharge from the affected side of horn and lachrymation were the  predominant clinical signs. The most affected age group was 6-10 years (52.94%) and the left horn was more frequently involved (67.65%).  All the animals passed through thermography showed consistent higher temperature in affected than non-affected horns, proving it  a reliable non-invasive diagnostic tool. This was followed by surgical amputation of affected horn and histopathological confirmation,  which identified squamous cell carcinoma (6 cases) and other conditions like papilloma, dysplastic changes, myxomatous growths and  normal horn tissue without pathological changes.
Keywords: Cattle; Histopathology; Horn cancer; Surgical management; Thermography